2022
DOI: 10.1371/journal.pone.0277240
|View full text |Cite
|
Sign up to set email alerts
|

Educational intervention and livestock ownership successfully improved the intake of animal source foods in 6–23 months old children in rural communities of Northern Ethiopia: Quasi-experimental study

Abstract: Background Animal source foods (ASFs) are rich in high-quality proteins, including essential amino acids and highly bioavailable micronutrients vital for child growth and cognitive development. But, the daily consumption of ASFs among 6–23 months old children is very low in Tigray, Northern Ethiopia. Objective The study aimed to assess the effectiveness of nutrition education intervention to improve the consumption of ASFs among 6–23 months old children from rural communities with strict religious fasting tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Furthermore, such households consider slaughtering livestock during fasting periods a major violation of their religious doctrine [44]. Nonetheless, this was in conflict with another study that reported higher price but not fasting as a main constraint to egg consumption by young children who were from Orthodox households [33].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, such households consider slaughtering livestock during fasting periods a major violation of their religious doctrine [44]. Nonetheless, this was in conflict with another study that reported higher price but not fasting as a main constraint to egg consumption by young children who were from Orthodox households [33].…”
Section: Discussionmentioning
confidence: 97%
“…This 10-percentage point increase in proportion of ASF consumption over the course of three back-to-back EDHSs could be the result of interventions that encouraged livestock production and local livestock markets, programs that raised awareness on nutritional benefits of ASFs, and community based projects that carried behavioral change components. For instance, a recently published work witnessed that provision of age-appropriate educational interventions for mothers increased the consumption of ASFs among children aged 6-23 months from rural communities of Tigrai [33].…”
Section: Discussionmentioning
confidence: 99%